28 The Quest to Identify Biomarkers of Long-Term Outcome in the Newborn. (October 2012) - Hyde, MJ; Modi, N
Abstract : We know that many events in the perinatal period have lifelong health implications. Work from animal models, and limited human data, suggest that deleterious long-term outcomes could be prevented by intervention in the neonatal period. While many studies of early life interventions are currently ongoing, outcome measures have to be in the short to medium term, even though the greatest impact of these interventions may not become apparent until well into adulthood. We are currently looking for biomarkers which can be measured non-invasively in the short term, but which have a strong association with long term outcome and may therefore provide indications of what the long-term effect of our experimental intervention may be. Methods currently being investigated include metabolomic technologies (using multi-component NMR/GCMS/LCMS platforms), genetic analysis using buccal swabs; in vivo magnetic resonance imaging and spectroscopy to measure metabolites in the liver and brain.